Biotechnology in agriculture and food processing : (CRC Press, 2014)
An instructive and comprehensive overview of the use of biotechnology in various agriculture and food applications, this book discusses the current status of applications for improving quality and productivity of agriculture and food products. It discusses plant tissue culture techniques, genetic engineering in food ingredient production, bio-fertilizers, bio-pesticides, enzymes, genetically modified foods etc. The book is divided into four parts: fundamental concepts, biotechnology in agriculture, biotechnology in food processing and biotechnological management of crop residues and waste/by products of agro industries